Conflict between physical analysis and mathematics causing failure: A case on diode circuits - Erawan Kurniadi; Arif Hidayat; Supriyono Koes Handayanto; Edi Supriana; Tantri Mayasari (Momentum: Physics Education Journal, 2024)
This study aims to describe the causes of students' failures in solving diode circuit problems. Research data were obtained through tests, dialogs, and interviews with 12 students of the physics education study program at Universitas PGRI Madiun. The research began by providing diode circuit test questions. Referring to the answers to the diode circuit test questions, an investigation was conducted through a basic circuit mastery test, followed by dialogs and interviews. The data from the test results, dialogs, and interviews in this study led to the conclusion that the common causes of students' failures in solving diode circuit problems are the inability to apply Ohm's law and Kirchhoff's law correctly, as well as the inconsistency and lack of systematic application of basic circuit concepts. A specific finding regarding the causes of failure in solving diode circuit problems is the conflict between physical and mathematical analyses. Based on the common causes of students' failures in solving diode circuit problems, a series of conceptual scaffolding needs to be designed. In conceptual scaffolding, complex circuits are transformed into several basic circuits to facilitate scaffolding for each basic concept. Procedural scaffolding needs to be designed to address failures resulting from the conflict between physical and mathematical analyses. One necessary step in procedural scaffolding is confirming answers using Kirchhoff's law.